UPAYA MENINGKATKAN HASIL BELAJAR PAI SISWA V SD NEGERI 003 TASIK JUANG MELALUI MODEL PEMBELAJARAN GROUP INVESTIGATION - Teni, Teni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This study aims to improve student learning outcomes of PAI through the Group Investigation learning model. This research is a classroom action research conducted at SDN 003 Tasik Juang. The subjects of this study were 30 people. The research will be carried out from August to September 2019. The research instrument used was an observation sheet and a test of learning outcomes. The results showed an increase in student learning activities and outcomes with a percentage of student activities in the first cycle of 57.5% with enough categories increased to 72.5% with a high category, student learning outcomes in the first cycle showed as many as 17 students or 56.7% who meet the KKM value set with an average learning outcome of 64.5 which is included in the category of being increased in the second cycle which shows as many as 24 students or 80% have met the KKM with an average of 75.3 which is included in the high category. Based on these results it can be concluded that the learning model of Group Investigation can improve the learning outcomes of PAI SDN 003 Tasik Juang students.